Stochastic Volatility: Origins and Overview. - Shephard, N; Andersen, T (Oxford-Man Institute of Quantitative Finance, 2008)
In this paper we review the history and recent developments of stochastic volatility, which is the main way financial economists and mathematical finance specialists model time varying volatility.